Synthesizing Co3O4 as anode material by thermal decomposition of metal organic framework - Low, Pearlyn Jia Wen (2018)
Technology in energy storage is constantly improving and evolving to satisfy the demand for storage of high energy in electronic devices. Various methods of synthesis and morphologies of anode materials have been researched intensively to build a more efficient Lithium Ion Battery (LIB). These new materials can counter the drawbacks faced by the original materials. This project focuses on synthesizing Co3O4 porous nanocages as an anode material for LIBs, where they are produced by thermal decomposition of metal cyanide coordination polymer. The obtained samples are characterized by SEM, TEM, XRD, XPS and CV analysis. The results obtained shows that Co3O4 porous nanocage has a size of 200 nm on average and are evenly distributed. In the process of long term lithium ion intercalation, the porous nanocages are able to retain the structural integrity and enable fast transport of lithium ions. Therefore, Co3O4 porous nanocage shows remarkable capacities, cycling stability and rate capability during the usage in LIBs. A high initial discharging and charging capacity of 1890 mAhg-1 and 1214 mAhg-1 is exhibited when Co3O4 porous nanocage is being used as an anode material for LIBs and being placed under a current rate of 0.1 Ag-1. At current rate of 10.0 Ag-1, excellent cycling capability is also displayed with a capacity of 523 mAhg-1 even after 150 cycles. The outstanding electrochemical performance of the electrode is attributed to the hollow porous structure.